Pengembangan Petunjuk Praktikum Biologi SMA melalui Metode Daring untuk Meningkatkan Keterampilan Proses Sains Siswa - Ida Royani; Ali Imran (Bioscientist : Jurnal Ilmiah Biologi, 2020)
The purpose of this study was to develop online methodology for high school biology practicum instructions and their effectiveness on students' science process skills. The subjects in this study were students of class X IPA SMA Al-Hamzar Tembeng Putik, Wanasaba District, East Lombok Regency. The type of research used is development research that produces products in the form of high school biology practicum instructions with online methods. The development procedure carried out in this study is in accordance with the steps based on the Borg & Gall model, with the following stages: 1) research and data collection; 2) planning; 3) development of the initial product draft; 4) initial field trials; 5) revised trial results; 6) field test of the main product; 7) product revision; 8) wide-scale field trials / feasibility tests; 9) final product revision; and 10) dissemination and implementation. This research is only up to the 7th stage. The research instrument used was the observation sheet and the validation sheet. The results showed that the high school biology practicum guide developed using the online method, based on the results of the validation that has been done, the score is 2.96 which is included in the valid category. As for the students' science process skills, the score was 70.5 in the skilled category, 81.5 in the highly skilled category, and 92 in the very skilled category.